Samanburður á árangri og fylgikvillum kransæðavíkkana hjá konum og körlum - Ragnar Danielsen; Kristján Eyjólfsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2003)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Introduction: The literature gives contradictory findings as to whether percutaneous coronary intervention (PCI) is equally successful in women and men. The objectives of this study were to compare between the sexes success and complications after PCI in Iceland. Methods: During the years 1987 to 2000 a total of 3355 PCI´s were performed, 798 (24%) in women and 2557 (76%) in men. Detailed records are held for all patients regarding clinical background, the outcome of PCI and in-hospital complications, and these were retrospectively assessed. Results: Compared with men, relatively more women were older than 65 years, hypertensive, hyperlipidemic, and non-smokers, but the prevalence of diabetes was similar. A prior history of myocardial infarction, or thrombolytic therapy was comparable for the sexes, while women less frequently had a history of a previous coronary bypass operation or PCI. Unstable angina pectoris was more common in women, they more often underwent subacute PCI, and were less likely than the men to have 3-vessels disease. PCI on two or more lesions, restenosis, or vein grafts, was comparable in the sexes. The primary success rate for PCI was comparable in women and men (93% versus 91%; p=0.06), and the use of stents was similar. Complications after PCI and in-hospital mortality (0.5% versus 0.3%; NS) was equally frequent, with the exception that women had more groin bleeding at the entry-site (1.25% versus 0.12%; p<0.001) and pseudoaneurysms (2.1% versus 0.6%; p<0.001). Conclusion: The primary success of PCI in Iceland is similar in the sexes. In-hospital mortality is low and complications comparable, with the exception that women more frequently developed entry-site groin sequels than men. Markmið: Umdeilt er hvort árangur kransæðavíkkana sé jafn góður hjá konum og körlum. Tilgangur þessarar rannsóknar var að bera saman milli kynjanna árangur og fylgikvilla eftir kransæðavíkkunaraðgerð hér á ...